Efficacy Comparison of Tenofovir and Entecavir in HBeAg-Positive Chronic Hepatitis B Patients with High HBV DNA. (1st March 2016) - Shi, Hong; Huang, Mingxing; Lin, Guoli; Li, Xiangyong; Wu, Yuankai; Jie, Yusheng; Chong, Yutian
Abstract : Objectives . To compare entecavir (ETV) and tenofovir disoproxil fumarate (TDF) effects in chronic hepatitis B (CHB) patients with high HBV DNA. Method . 96 patients treated initially with tenofovir (TDF group) or entecavir (ETV group) were included in this retrospective study. The following parameters were assessed: HBeAg and hepatitis B e antibody (anti-HBe) status, serum alanine aminotransferase (ALT), and HBV-DNA levels at weeks 4, 12, 24, 36, 48, 60, 72, and 96; time to ALT normalization, undetectable HBV-DNA levels, and HBeAg seroconversion; total duration of follow-up and adverse reactions. Results . The patients included 66 (69%) and 30 (31%) individuals administered ETV and TDF, respectively, comprising 75% males. They were 35.1 ± 4.5 and 33.7 ± 4.6 years old in ETV and TDF groups, respectively. At 36 weeks, the response rate was significantly higher in the TDF group than in ETV treated patients (90% versus 69.7%, p = 0.03 ). At 48 weeks, less patients administered ETV showed undetectable HBV-DNA levels compared with the TDF group (86.4% versus 96.7%), a non-statistically significant difference (p = 0.13 ). Only 1 ETV treated patient developed virological breakthrough at 48–96 w. No adverse reactions were found. Conclusion . ETV and TDF are comparable in efficacy and safety to suppress HBV-DNA replication in HBeAg-positive CHB patients with high HBV DNA.